Interfacial mechanical behavior of 3D printed ABS. Issue 30 (20th April 2016) - Cole, Daniel P.; Riddick, Jaret C.; Iftekhar Jaim, H. M.; Strawhecker, Kenneth E.; Zander, Nicole E.
ABSTRACT: We describe an experimental approach for characterizing the local mechanical behavior of acrylonitrile butadiene styrene (ABS) structures processed through fused deposition modeling. ABS test specimens processed in various build orientations were subject to multiscale mechanical tests as well as local morphology and chemical analyses. Instrumented indentation, local dynamic mechanical analysis, and atomic force microscopy tests were used to explore the mechanical behavior and morphology of build surfaces and weld interfaces. An interfacial stiffening effect was found for the majority of the specimens tested, with up to a 40% increase in the indentation elastic modulus measured with respect to the build surfaces. Raman spectroscopy mapping of the interfacial areas revealed ∼30% less butadiene/styrene and butadiene/acrylonitrile ratios with respect to analysis of the build surfaces. The results provide insight into the multiscale behavior of additive manufactured structures and offer the potential to guide processing–structure–property understanding of these materials. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43671. Abstract :